The use of artificial intelligence and machine learning monitoring to safely administer a fluid-restrictive goal-directed treatment protocol to minimize the risk of transfusion during major spine surgery of a Jehovah’s Witness: a case report - Denn, Sara; Schneck, Emmanuel; Jablawi, Fidaa; Bender, Michael; Schmidt, Götz; Habicher, Marit; Uhl, Eberhard; Sander, Michael; Justus Liebig University Giessen (My University, 2022)
Background: The Hypotension Prediction Index (HPI) displays an innovative monitoring tool which predicts intraoperative hypotension before its onset. Case presentation: We report the case of an 84-year-old Caucasian woman undergoing major spinal surgery with no possibility for the transfer of blood products given her status as a Jehovah’s Witness. The hemodynamic treatment algorithm we employed was based on HPI and resulted in a high degree of hemodynamic stability during the surgical procedure. Further, the patient was not at risk for either hypo- or hypervolemia, conditions which might have caused dilution anemia. By using HPI as a tool for patient blood management, it was possible to reduce the incidence of intraoperative hypotension to a minimum. Conclusions: In sum, this HPI-based treatment algorithm represents a useful application for the treatment of complex anesthesia and perioperative patient blood management. It is a simple but powerful extension of standard monitoring for the prevention of intraoperative hypotension.
Keywords: Jehovah’s Witnesses; Blood transfusion; Hemodynamic monitoring; Case report; Hypotension; Hemodilution; ddc:610